PENGARUH LINGKUNGAN, PENDIDIKAN KEWIRAUSAHAAN, DAN PENGGUNAAN E-COMMERCE TERHADAP PENINGKATAN MINAT BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ISLAM MALANG - Hendriyanto Rusli; Noor Shodiq Askandar; Abdul Wahid Mahsuni (Universitas Islam Malang, 2022)
This study aims to determine the effect of the environment, entrepreneurship education, and the use of e-commerce to increase interest in entrepreneurship. The object of this research is the students of the Faculty of Economics and Business, Islamic University of Malang with a sample of 84 students with notes that have taken entrepreneurship courses. The sampling technique used was purposive sampling. Data collection techniques using questionnaires and data analysis tools. Based on the results of research analysis partially the environment has a significant effect on interest in entrepreneurship. While partially entrepreneurship education has a significant effect on interest in entrepreneurship. While partially e-commerce has a significant effect on interest in entrepreneurship.Keywords: Entrepreneurship Education, E-Commerce and Interest in Entrepreneurship